Intermediate Results of Radar Backscatter Measurements from Summer Sea Ice. - Gogineni,S; Onstott,R G; Moore,R K; Chancellor,J (1984)
A helicopter-borne scatterometer (HELOSCAT) was used to measure radar backscatter from sea ice under summer conditions near Mould Bay, N.W.T., Canada, in June and July 1982. These measurements were made at selected frequencies between 1 and 17 GHz, and at angles between 5 deg and 60 deg with like and cross-polarizations. Multiyear ice (MYI) can be distinguished form first-year ice (FYI) using the profiles acquired by flying the helicopter along selected scan lines at 5.2, 9.6 adn 13.6 GHz during early and late summer. Because of wet snow and ice on the surface, producing reduced volume scatter, there is lower backscatter from MYI during summer that during winter. Because of superimposed ice, the backscatter from FYI during early summer is slightly higher than that during other seasons. Its backscatter is higher than that of MYI for the early part of summer, but as summer progresses, FYI backscatter reduces and eventually becomes lower than that from MYI. Results indicate that higher frequencies in Ku- and X-bands are not better than lower frequencies in C-band for discriminating basis ice types during summer. Backscatter from MYI and FYI increased with frequency, and the contrast between FYI and MYI increased with decreasing frequency during late summer.